In-Depth Analysis And Exploration Of Essential Aspects In Employee Performance And Job Satisfaction At PT Paskomnas Niaga Utama - Valentine Theresia Simamora; Abdullah, Muhammad; Hary Mulyadi; Wahid Akbar Basudani; Gani Wiharso (Jurnal Ekonomi, 2024)
This study aims to analyze the relationship between compensation, work environment, job satisfaction, and employee performance at PT Paskomnas Niaga Utama using a path analysis model with Smart PLS software version 4.1.0.0. The exogenous variables considered are compensation and work environment, while the endogenous variables examined are job satisfaction and employee performance. This research also investigates the mediating role of job satisfaction in the relationship between compensation, work environment, and employee performance. The study utilizes a non-probability sampling approach, specifically a saturated sample of 75 respondents, and adopts a quantitative post facto method. The findings reveal that compensation and work environment have a significant positive impact on job satisfaction and employee performance. Additionally, job satisfaction plays a crucial mediating role in the relationship between compensation, work environment, and employee performance. These results contribute to a deeper understanding of the factors influencing job satisfaction and employee performance within the context of PT Paskomnas Niaga Utama. The practical implications of this research emphasize the importance for companies to prioritize compensation strategies and create conducive work environments to enhance employee satisfaction and performance, ultimately facilitating the achievement of organizational goals. However, it's essential to acknowledge the limitations of the study, such as the reliance on a specific sampling method and the potential for other unexplored variables to influence the outcomes. Further research could address these limitations and provide a more comprehensive understanding of the dynamics at play.